FREQUENCY OF ABNORMAL HEPATIC VENOUS WAVEFORMS IN CIRRHOTIC PATIENTS: Abnormal Hepatic Venous Waveforms - Andrabi, Syed Atif Hussain; Nafees, Muhammad; Haq, Irfan ul (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the frequency of abnormal hepatic venous waveforms in patients suffering from hepatic cirrhosis.Study Design: Cross sectional.Place and of Study Duration: Shafique Medical Centre Quetta & Radiology Department Combined Military Hospital, Quetta from December 15th 2009 to July 15th 2010.Material and Methods: The instrument used in this study was Toshiba Eccocee SSA-340A and ALOKA SSD-5000 doppler ultrasound machines with linear and convex probes. Hepatic venous Doppler was performed with convex 3-5 MHz probe. Hepatic venous Doppler examination was performed by two radiologists (operators) on all the 135 patients with positive HCV, HBV, chronically raised amino transferase level and clinical & radiological features of cirrhosis, who independently and blindly recorded their findings. Non-probability, purposive sampling was done. After Doppler ultrasonographic examination liver biopsy & histopathology of all the patients was performed.  Data from each patient was collected on designed form for age, gender, types of hepatic vein waveforms and grades/severity of liver cirrhosis on histopathology.Results: 135 patients with maximum 50 years and minimum 41 years of age have mean age of 46.79 ± 2.37. Out of 135 patients in 103 (76.3%) Type 1 (Triphasic) flow was observed in 3%, Type II (Biphasic without reduced oscillation) flow was observed in 29.6%, type III (Biphasic with reduced oscillation) flow was observed in 34.1% and type IV (Monophasic) flow noted in 33.33 %.  There was significant correlation between hepatic venous waveform and severity of cirrhosis on histopathology (r=0.887, p< 0.001)Conclusion: Hepatic venous Doppler is noninvasive tool which can be employed to assess the types of abnormal hepatic venous waveforms in patients with hepatic cirrhosis. There is significant correlation between hepatic venous waveform and severity of cirrhosis on histopathology.